De novo super-early progeny in interspecific crosses Pisum sativum L. × P. fulvum Sibth. et Sm - Hatice Sari (Nature Portfolio, 2021)
Abstract Earliness in crop plants has a crucial role in avoiding the stress of drought and heat, which are the most important challenging stressors in crop production and are predicted to increase in the near future due to global warming. Furthermore, it provides a guarantee of vegetable production in the short growing season of agricultural lands in the northern hemisphere and at high altitudes. The growing human population needs super early plant cultivars for these agricultural lands to meet future global demands. This study examined de novo super-early progeny, referred to as much earlier than that of the earlier parent, which flowered in 13–17 days and pod setting in 18–29 days after germination, discovered in F2 and studied up to F5 derived from interspecific crosses between garden pea (P. sativum L.) and the most distant relative of pea (P. fulvum Sibth. et Sm.). De novo super-early progeny were found to be earlier by about one month than P. sativum and two months than P. fulvum under short day conditions in the F5 population. In respect of days to flowering and pod setting, de novo super-early progeny had a relatively high level of narrow sense heritability (h 2 = 82% and 80%, respectively), indicating that the selections for earliness in segregating populations was effective for improvement of extreme early maturing varieties. De novo super-early progeny could be grown under heat stress conditions due to the escape ability. Vegetable types were not only high yielding but also free of any known undesirable traits from the wild species, such as pod dehiscence and non-uniform maturity. It could be considered complementary to “speed breeding”, possibly obtaining more than six generations per year in a suitable climate chamber. Not only de novo super-early progeny but also transgressive segregation for agro-morphological traits can be created via interspecific crosses between P. sativum and P. fulvum, a precious unopened treasure in the second gene pool. Useful progeny obtained from crossing wild species with cultivated species reveal the importance of wild species.